Distribusi Spasial Habitat Larva, Kepadatan Anopheles sp dan Kasus malaria di Kampung Kiren Distrik Bonggo Kabupaten Sarmi - Henny Sesanti Budi Hastuty; Theresie Chindyana Herman; Irfan Pabarri; Hiskia Batara Randa; Yusuf Syerim Bisim (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2021)
Geographic Information Systems (GIS) can be used to describe health problems, one of the problem can be described is malaria. Malaria is still a major health problem for people in Papua. Papua Annual Parasite Incidence (API) is the highest in Indonesia (Kemenkes RI, 2017). This study aims to describe the spatial distribution of larval habitat, adult mosquito density, and the distribution of malaria patients in January-April 2019 in Kiren Village, Bonggo District. The results showed that there were 29 positive habitats of Anopheles sp larvae, consisting of puddles (69.0%), sago marsh (3.4%), artificial ponds (13.8%), and gutters (13, 8%), the habitat is spread almost evenly throughout the Kiren Village area. Larvae species caught were: An.punctulatus (17.2%), An.maculatus (31.0%), An.farauti (6.9%), An.telatelatus (3.4%), and An.longirostris (31.0%) and not identified 10.3%. The highest density of adult mosquitoes is 7 mosquito/person/night, the lowest is 1.5 mosquito/person/night, with an average of 3.6 mosquito/person/night. Adult mosquito species caught : An.maculatus (37.9%), An.karwari (10.3%), An.punctulatus (31.0%), An.farauti (13.8%), and An.longoristris (6.9%). Malaria patients highest based on  age  group is in the 20-44 years (39.3%), and by sex in the female group (62.5%). The conclusions of this study are as follows: the highest larval habitat is puddles, the most caught larvae species are An.maculatus and An.longirostris, high mosquito density/ high MBR, adult mosquito species are mostly caught is An.punctulatus, the highest malaria patients based on age group is in the 20-44 years old and based on sex from female group.